2018
DOI: 10.1103/physrevb.98.205307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion-implantation-induced defects and Mg dopants on the thermoelectric properties of ScN

Abstract: For applications in energy harvesting, environmentally friendly cooling, and as power sources in remote or portable applications, it is desired to enhance the efficiency of thermoelectric materials. One strategy consists of reducing the thermal conductivity while increasing or retaining the thermoelectric power factor. An approach to achieve this is doping to enhance the Seebeck coefficient and electrical conductivity, while simultaneously introducing defects in the materials to increase phonon scattering. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
(101 reference statements)
2
25
0
Order By: Relevance
“…It has also been shown that the Fermi level shifts towards the conduction band when the materials are doped with O. A study with Mg ion implantation with higher oxygen content retained n-type behavior [43]. Furthermore, it was noted in Figure 1c,d, Figure 2c,d, and Figure 3c,d that the highest occupied state is shifted into the conduction band in ScTaN 2 , ScNbN 2 , and ScVN 2 .…”
Section: Computational Detailsmentioning
confidence: 85%
See 1 more Smart Citation
“…It has also been shown that the Fermi level shifts towards the conduction band when the materials are doped with O. A study with Mg ion implantation with higher oxygen content retained n-type behavior [43]. Furthermore, it was noted in Figure 1c,d, Figure 2c,d, and Figure 3c,d that the highest occupied state is shifted into the conduction band in ScTaN 2 , ScNbN 2 , and ScVN 2 .…”
Section: Computational Detailsmentioning
confidence: 85%
“…A study with Mg ion implantation with higher oxygen content retained n-type behavior. [43] Furthermore, it was noted in Figures 1c,d, 2c,d, and 3c,d that the highest occupied state is shifted into the conduction band in In terms of the transport distribution function, it has been theoretically shown that for a given lattice thermal conductivity, ZT is maximized when the transport distribution function consists of a Dirac delta function just above or below the Fermi level [41]. This is an idealized situation that does not correspond to real materials, but still a narrow distribution around the Fermi level will increase ZT [41,42].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Finally, the amplitude and phase experimental profiles were fitted according to a standard Fourier diffusion law to extract the thermal conductivity of the CaMnO 3 films [25][26][27][28]. More details on the procedure of fit and extraction of the thermal conductivity of the film with a low thermal conductivity layer in between the gold and sapphire substrate can be found elsewhere [29].…”
Section: Methodsmentioning
confidence: 99%
“…(2). This can be done by discovering new materials or optimising existing ones through techniques such as alloying or doping, where doping can also be used to tune the semiconductor type 911 .In the commercial world, roll-to-roll (R2R) systems are used to create large areas of high-throughput flexible coatings, and can be used to manufacture flexible electronics. Rolls of flexible materials, referred to as a web, are gradually unwound, coated and rewound, with the coated processes potentially consisting of multiple steps/layers.…”
Section: Introductionmentioning
confidence: 99%